Riba Menurut Al-Quran dan Hadits dalam Perspektif Ekonomi Islam - Cece Nurhikmah (LP2M STAI Al-Muhajirin Purwakarta, 2021)
This paper examines the prohibition of usury according to the Qur'an and hadith. It is explained in the Al-Quran surah Ar-Rum verse 13, An-Nisa verse 160-161, Ali Imran verse 130 and al-Baqarah verse 275-279. Riba is an additional requirement for a person in a sale and purchase transaction of debts of all types of goods, whether in the form of jewelry, food, plants and fruits as well as certain objects that can be exchanged in a certain way. The purpose of writing the prohibition of usury is to find out the interpretation of usury according to the Qur'an and hadith in view of the law of usury and to analyze usury both from the side of asbabub nuzul, asbabub wurud, etc. The method used in this article on the prohibition of usury uses a qualitative approach. This type of research uses a literature review, namely research in which all data comes from written materials such as books, manuscripts, journals, and documents related to usury. The method used is descriptive-analytic method, namely the research method by describing and analyzing all the data that has been obtained. The results of this study are based on asbabun nuzul, verse, ababul wurud hadith, it is clear that usury is haram.